Techno-Economic Sizing of a community battery to provide community energy billing and additional ancillary services. (June 2021) - Elkazaz, Mahmoud; Sumner, Mark; Naghiyev, Eldar; Hua, Zhihao; Thomas, David W.P.
Abstract: This paper presents a novel sizing methodology (energy and power rating) for a Community Battery Energy Storage System (CBESS). The CBESS provides management of the local community energy, and also delivers ancillary services. The investigation considers the economic performance of the CBESS over a 20 year lifetime, including potential revenue when the CBESS provides services for the National Grid such as participation in the Capacity Market and Dynamic Firm Frequency Response services. Furthermore, an economic study is performed to investigate if an addition revenue could be obtained if the CBESS is used to provide more than one service. The methodologies presented for sizing the battery for communities are based on real historic data of several households. The results demonstrate that for a 20 year period, using a 1000 kWh/500 kW CBESS to provide more than one service in any single day achieves the highest value of internal rate of return (10.15%), compared to using the same CBESS to provide only one service for the whole day. Highlights: A novel sizing methodology for a community battery storage, has been presented. Optimal battery sizing reduced the annual community bill by 45%, and maximized the PV self-consumption to 93.5%. A 1000 kWh/500 kW community battery can achieve 10.15% internal rate of return. A community battery achieves 16% IRR when provides firm frequency response service. The investment in the 1000 kWh/500 kW battery achieves a highest IRR value.